2003
DOI: 10.1189/jlb.1002506
|View full text |Cite
|
Sign up to set email alerts
|

Fever-like thermal conditions regulate the activation of maturing dendritic cells

Abstract: Fever is one of the most frequent clinical signs encountered in pathology, especially with respect to infectious diseases. It is currently thought that the role of fever on immunity is limited to activation of innate immunity; however, its relevance to activation of adaptive immunity remains unclear. Dendritic cells (DCs) that behave as sentinels of the immune system provide an important bridge between innate and adaptive immunity. To highlight the role of fever on adaptive immunity, we exposed murine bone mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
38
2
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 39 publications
4
38
2
1
Order By: Relevance
“…DC were generated from proliferating bone marrow progenitors from male BALB/c (H-2 d ) and C57BL/6 (H-2 b ) mice, as described previously (18). DC were negative for monocyte-macrophage (CD14), B cell (CD45R/ B220), and granulocyte (Gr-1) marker, and exhibited a phenotype of my-…”
Section: Generation Of Mouse Bone Marrow-derived DCmentioning
confidence: 99%
“…DC were generated from proliferating bone marrow progenitors from male BALB/c (H-2 d ) and C57BL/6 (H-2 b ) mice, as described previously (18). DC were negative for monocyte-macrophage (CD14), B cell (CD45R/ B220), and granulocyte (Gr-1) marker, and exhibited a phenotype of my-…”
Section: Generation Of Mouse Bone Marrow-derived DCmentioning
confidence: 99%
“…In this regard, the fever thermal component confers protection to the host in defense against microbial pathogens by enhancing the innate immune response and, in particular, activating neutrophils (11,12). Moreover, hyperthermia may lead to direct maturation of dendritic cells in vitro and in vivo, and this effect correlates well with an improved immunostimulatory activity mediated by these cells (13)(14)(15)(16). Despite these intriguing observations, temperature manipulation is rarely considered in the context of most experimental immunological investigations.…”
mentioning
confidence: 99%
“…Fever is a part of the innate immune response in vivo and can aid the immune defense by impairing the viability of pathogens with strict temperature preferences or by enhancing immunological reactions (reviewed in ref- erence 38). Previous studies indicate that fever-range temperature in vivo and in vitro augments antigen presentation and coreceptor expression and skews antigen-presenting cells (APCs) toward activation, in concert with augmented T cell responsiveness and Th1 bias (5,6,17,33).…”
mentioning
confidence: 99%
“…Fever is a part of the innate immune response in vivo and can aid the immune defense by impairing the viability of pathogens with strict temperature preferences or by enhancing immunological reactions (reviewed in reference 38). Previous studies indicate that fever-range temperature in vivo and in vitro augments antigen presentation and coreceptor expression and skews antigen-presenting cells (APCs) toward activation, in concert with augmented T cell responsiveness and Th1 bias (5,6,17,33).One of the major challenges of CMI assays-and IGRAs, in particular-is achieving a consistent and strong response (i.e., high sensitivity) without generating nonspecific immune activation (i.e., compromising specificity).We and others have demonstrated that, compared to T cell responses, the APCs interacting with the specific T cells generate stronger chemokine and cytokine signals that could enable simpler or more sensitive readouts of CMI assays (reviewed in reference 24). In several studies, the chemokine IFN-␥-induced protein 10 (IP-10) has shown promise as a novel marker for immunodiagnosis of infection with M. tuberculosis in both children and adults (1,13,15,(21)(22)(23)30).…”
mentioning
confidence: 99%